Platelet-VWF complexes get the chop - Berndt, Michael; Andrews, R. (American Society of Hematology, 2008)
In this issue of Blood, Shim and colleagues define a dual role for platelet glycoprotein (GP)Iba (the major ligand-binding subunit of the GPIb-IX-V complex) in regulating ADAMTS13-mediated cleavage of von Willebrand factor (VWF) under shear: it alleviates an inhibitory effect of the VWFA1 domain on cleavage of the A2 domain, 1 and it allows tensile force to be exerted on the A2 domain through at least 2 platelets binding per VWF multimer via the A1 domain (see figure).